Audit Characteristics and Financial Reporting Timeliness of Nigerian Listed Non-Financial Institution - Inneh, Eghosa; FAKUNLE, Isaiah Omotayo; BUSARI, Romoke Rafiat; OLATUNJI, Ibrahim Gbenga (Journal of Economics and Behavioral Studies, 2022)
The management is accused of opportunistic behavior and financial report delays following the global financial scandal. Consequently, studies examine the effect of client-specific characteristics on financial report timeliness, and Nigeria is not an exemption. Recent studies focus on the effect of auditor’s attributes in mitigating or explaining the rationale for the financial reporting delay. However, limited studies exist in Nigeria on the effect of audit characteristics on financial reporting timeliness in non-financial institutions. Our study contributes to knowledge by examining the effect of audit characteristics on the financial reporting timeliness in the Nigerian listed non-financial institution. We select 450 firm-year observations from 2011 to 2020 using a purposive sampling technique and estimate the model using the Ordinary Least Square Method (OLS). The result reveals that audit price and audit firm size positively affect financial reporting timeliness, while audit tenure is negative but insignificantly related to financial reporting timeliness. Our study concludes that delivering the financial report to the users takes longer when the auditors charge higher fees, reflecting an increase in auditors’ workload resulting from additional audit risk and procedure. Also, large audit firms take a long time to communicate financial reports taking due care in forming audit opinions to ensure audit independence and reduce the litigation risk arising from the audit assignment